Strategi Pengurus Keamanan dalam Menyelesaikan Konflik Antar Santri yang Berlatar Belakang Budaya Berbeda di Pondok Pesantren - Alfan Fadli; Olyvia Zalianti; Sintia Devinta Wati; Julian Liew; Muallimin Muallimin (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Conflicts that arise in pesantren are often triggered by cultural, normative, and habitual differences among santri from various regions. This study aims to identify and analyze the strategies employed by the security management in resolving conflicts among santri with different cultural backgrounds at Pondok Pesantren Darus Sholah Jember. The research method used is a descriptive qualitative approach with data collection techniques through participatory observation, in-depth interviews, and document study. The results show that the pesantren management uses mediation, educational approaches, and rule formation to manage conflicts. Support from the pesantren leadership and religious values emphasizing brotherhood are key supporting factors, while communication barriers among the santri remain a challenge that needs to be addressed. This study contributes to understanding conflict management in religious-based educational institutions.